(Un)preferential treatment: 'Special' and particularistic citizenship norms in the EU28, 1992–2015. Issue 1 (2nd January 2018) - Sredanovic, Djordje
Abstract: Through the analysis of citizenship legislation in the 28 EU member states between 1992 and 2015, this article explores 'special' and particularistic citizenship norms that are usually excluded from comparative citizenship legislation analyses. Such norms are identified by their application to small groups or exceptional cases, and by the presence of normative analyses that criticize such norms as opposed to universalism. Six categories – ethnicity, special merits, special demerits, norms for EU citizens, stateless individuals and refugees, and investors – are identified, with special merits and ethnicity showing a very high diffusion in the 28 member states. The article further explores the role of the political parties in government in the introduction of 'special' norms, showing that while both center-right and center-left governments are more likely to introduce than to abolish 'special' norms, center-left governments are comparatively less likely to introduce such norms.